Mpox vaccination willingness, determinants, and communication needs in gay, bisexual, and other men who have sex with men, in the context of limited vaccine availability in the Netherlands (Dutch Mpox-survey) - Nicole H. T. M. Dukers-Muijrers; Nicole H. T. M. Dukers-Muijrers; Ymke Evers; Ymke Evers; Veja Widdershoven; Veja Widdershoven; Udi Davidovich; Udi Davidovich; Philippe C. G. Adam; Philippe C. G. Adam; Eline L. M. Op de Coul; Paul Zantkuijl; et al. (Frontiers Media S.A., 2023)
IntroductionIn the 2022 multicountry mpox (formerly named monkeypox) outbreak, several countries offered primary preventive vaccination (PPV) to people at higher risk for infection. We study vaccine acceptance and its determinants, to target and tailor public health (communication-) strategies in the context of limited vaccine supply in the Netherlands.MethodsOnline survey in a convenience sample of gay, bisexual and other men who have sex with men, including transgender persons (22/07-05/09/2022, the Netherlands). We assessed determinants for being (un)willing to accept vaccination. We used multivariable multinominal regression and logistic regression analyses, calculating adjusted odds ratios (aOR) and 95 percent confidence-intervals. An open question asked for campaigning and procedural recommendations.ResultsOf respondents, 81.5% (n = 1,512/1,856) were willing to accept vaccination; this was 85.2% (799/938) in vaccination-eligible people and 77.7% (713/918) in those non-eligible. Determinants for non-acceptance included: urbanization (rural: aOR:2.2;1.2-3.7; low-urban: aOR:2.4;1.4-3.9; vs. high-urban), not knowing mpox-vaccinated persons (aOR:2.4;1.6-3.4), and lack of connection to gay/queer-community (aOR:2.0;1.5-2.7). Beliefs associated with acceptance were: perception of higher risk/severity of mpox, higher protection motivation, positive outcome expectations post vaccination, and perceived positive social norms regarding vaccination. Respondents recommended better accessible communication, delivered regularly and stigma-free, with facts on mpox, vaccination and procedures, and other preventive options. Also, they recommended, "vaccine provision also at non-clinic settings, discrete/anonymous options, self-registration" to be vaccinated and other inclusive vaccine-offers (e.g., also accessible to people not in existing patient-registries).ConclusionIn the public health response to the mpox outbreak, key is a broad and equitable access to information, and to low-threshold vaccination options for those at highest risk. Communication should be uniform and transparent and tailored to beliefs, and include other preventive options. Mpox vaccine willingness was high. Public health efforts may be strengthened in less urbanized areas and reach out to those who lack relevant (community) social network influences.